New insight into the bark beetle ips typographus bacteriome reveals unexplored diversity potentially beneficial to the host - Peral-Aranega, Ezequiel; Saati-Santamaría, Zaki; Ayuso-Calles, Miguel; Kostovčík, Martin; Veselská, Tereza; Švec, Karel; Rivas, Raúl; Kolařik, Miroslav; García-Fraile, Paula (Environmental microbiome, 2023)
BACKGROUND: Ips typographus (European spruce bark beetle) is the most destructive pest of spruce forests in Europe. As for other animals, it has been proposed that the microbiome plays important roles in the biology of bark beetles. About the bacteriome, there still are many uncertainties regarding the taxonomical composition, insect-bacteriome interactions, and their potential roles in the beetle ecology. Here, we aim to deep into the ecological functions and taxonomical composition of I. typographus associated bacteria. RESULTS: We assessed the metabolic potential of a collection of isolates obtained from different life stages of I. typographus beetles. All strains showed the capacity to hydrolyse one or more complex polysaccharides into simpler molecules, which may provide an additional carbon source to its host. Also, 83.9% of the strains isolated showed antagonistic effect against one or more entomopathogenic fungi, which could assist the beetle in its fight against this pathogenic threat. Using culture-dependent and -independent techniques, we present a taxonomical analysis of the bacteriome associated with the I. typographus beetle during its different life stages. We have observed an evolution of its bacteriome, which is diverse at the larval phase, substantially diminished in pupae, greater in the teneral adult phase, and similar to that of the larval stage in mature adults. Our results suggest that taxa belonging to the Erwiniaceae family, and the Pseudoxanthomonas and Pseudomonas genera, as well as an undescribed genus within the Enterobactereaceae family, are part of the core microbiome and may perform vital roles in maintaining beetle fitness. CONCLUSION: Our results indicate that isolates within the bacteriome of I. typographus beetle have the metabolic potential to increase beetle fitness by proving additional and assimilable carbon sources for the beetle, and by antagonizing fungi entomopathogens. Furthermore, we observed that isolates from adult beetles are more likely to have these capacities but those obtained from larvae showed strongest antifungal activity. Our taxonomical analysis showed that Erwinia typographi, Pseudomonas bohemica, and Pseudomonas typographi species along with Pseudoxanthomonas genus, and putative new taxa belonging to the Erwiniaceae and Enterobacterales group are repeatedly present within the bacteriome of I. typographus beetles, indicating that these species might be part of the core microbiome. In addition to Pseudomonas and Erwinia group, Staphylococcus, Acinetobacter, Curtobacterium, Streptomyces, and Bacillus genera seem to also have interesting metabolic capacities but are present in a lower frequency. Future studies involving bacterial-insect interactions or analysing other potential roles would provide more insights into the bacteriome capacity to be beneficial to the beetle.
Keywords: Insect microbiome; Microbial ecology; Lignocellulolytic enzymes; Host-microbe interactions; Symbionts